Physiological characterisation of human iPS-derived dopaminergic neurons - Hartfield, E; Yamasaki-Mann, M; Ribeiro Fernandes, H; Vowles, J; James, W; Cowley, S; Wade-Martins, R (Public Library of Science, 2014)
Human induced pluripotent stem cells (hiPSCs) offer the potential to study otherwise inaccessible cell types. Critical to this is the directed differentiation of hiPSCs into functional cell lineages. This is of particular relevance to research into neurological disease, such as Parkinson's disease (PD), in which midbrain dopaminergic neurons degenerate during disease progression but are unobtainable until post-mortem. Here we report a detailed study into the physiological maturation over time of human dopaminergic neurons in vitro. We first generated and differentiated hiPSC lines into midbrain dopaminergic neurons and performed a comprehensive characterisation to confirm dopaminergic functionality by demonstrating dopamine synthesis, release, and re-uptake. The neuronal cultures include cells positive for both tyrosine hydroxylase (TH) and G protein-activated inward rectifier potassium channel 2 (Kir3.2, henceforth referred to as GIRK2), representative of the A9 population of substantia nigra pars compacta (SNc) neurons vulnerable in PD. We observed for the first time the maturation of the slow autonomous pace-making (<10 Hz) and spontaneous synaptic activity typical of mature SNc dopaminergic neurons using a combination of calcium imaging and electrophysiology. hiPSC-derived neurons exhibited inositol tri-phosphate (IP3) receptor-dependent release of intracellular calcium from the endoplasmic reticulum in neuronal processes as calcium waves propagating from apical and distal dendrites, and in the soma. Finally, neurons were susceptible to the dopamine neuron-specific toxin 1-methyl-4-phenylpyridinium (MPP+) which reduced mitochondrial membrane potential and altered mitochondrial morphology. Mature hiPSC-derived dopaminergic neurons provide a neurophysiologically-defined model of previously inaccessible vulnerable SNc dopaminergic neurons to bridge the gap between clinical PD and animal models.